Enzinger and Weiss's soft tissue tumors - Weiss, Sharon W; Goldblum, John R (Mosby, 2001)
Here\'s the fourth edition of the leading clinical reference on tumors of the muscle, fat and connective tissue, completely revised and expanded to reflect the latest developments and understanding of the field. Organized according to the most recent classification scheme, it offers outstanding coverage of pathology, prognostic variables, and modes of therapy. Features new chapters on immunohistochemistry and cytopathology and extensively revised chapters on molecular biology, genetics, and cytogenetics. \"The greatest strengths of the book are the comprehensive coverage, profuse illustrations, and clarity of the writing...the definitive work that every pathologist will consult.\" *Dermatopathology: Practical and Conceptual, review of previous edition
Keywords: Soft Tissue Neoplasms; nádory měkkých tkání; onkologie; patologie; Onkologie; nádory; Neoplasms; Lékařství